Two women arm-in-arm - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women arm-in-arm as they march in the National March on Washington for Lesbian and Gay Rights. The women on the right has her left arm up in the air and there are other women marching in the background.